Prevalence of risk factors of non-communicable diseases in a rural area of Bangladesh - Ahmed, Jasimuddin; Zaman, M Mostafa; Choudhury, Sohel R; Zissan, Tashfin; Ahmed, Mehedi Hasan; Ahmed, Masud (Cardiovascular Journal, 2017)
Background: Data on risk factors of non-communicable diseases (NCDs) are still inadequate Bangladesh. More data, especially from rural population because 70 percent of Bangladeshi people leave in rural area, are necessary to plan intervention and monitor progress of NCD control. The aim of the study was to determine distribution and prevalence of risk factors of NCDs in a rural adult population of Bangladesh. Method: A cross-sectional study targeting one adult (15 years or older) from each of 1088 households of a village was carried out in 2008. Among them 1011 participated. Information on age and education of the respondents and risk factors such as tobacco, fruit and vegetable intake, habit of added salt while taking the meal, blood pressure and waist circumference were obtained using standardized protocol. Results: Mean age of the subjects was 42.4 years. Age adjusted prevalence of tobacco consumption was 59.5% (smoking 31.0% and smokeless tobacco use 36.3%). More than nine in ten (92.8%) of the respondents consumed less than 5 serving of fruit and/or vegetables per day. Nine in ten (88.5%) used extra salt during meal. Prevalence of hypertension and central obesity was found 19.7% and 18.8% respectively. Conclusion: NCD risk factors are widely prevalent even in this rural population having a traditional agricultural lifestyle. Interventions those are appropriate to this kind of community are needed to be developed in Bangladesh. Cardiovasc. j. 2017; 9(2): 122-128